New species and new records of Cumacea (Crustacea: Peracarida: Cumacea) from mesophotic reefs of Puerto Rico and U.S. Virgin Islands, Caribbean Sea - Petrescu, Iorgu; Chatterjee, Tapas; Schizas, Nikolaos V. (Zootaxa, 2016)
The cumacean fauna of the Caribbean mesophotic reefs is remarkably rich but understudied. Herein, we present the description of 22 new species of the family Nannastacidae, including one from shallow reefs, 20 of them belonging to Cumella (Cumella) and two new species belonging to the subgenus Cumewingia. We have also included range extensions and new locations for ten previously known species of Cumella, two species in the genus Vaunthompsonia (family Bodotriidae) and one species in the genus Cubanocuma (family Nannastacidae). Taxonomic keys are provided for the western tropical Atlantic species of Cumella (Cumella) and Cumella (Cumewingia), separately for the adult males and females. Large sampling efforts and careful systematic studies, even in relatively well-characterized regions such as the Caribbean, can yield a surprising number of new discoveries. Our current findings emphasize our previous assertion that the mesophotic reefs are treasure troves of undiscovered benthic fauna and might be qualified as biodiversity hotspots.